If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(x + 8) = 35 Reorder the terms: -7(8 + x) = 35 (8 * -7 + x * -7) = 35 (-56 + -7x) = 35 Solving -56 + -7x = 35 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '56' to each side of the equation. -56 + 56 + -7x = 35 + 56 Combine like terms: -56 + 56 = 0 0 + -7x = 35 + 56 -7x = 35 + 56 Combine like terms: 35 + 56 = 91 -7x = 91 Divide each side by '-7'. x = -13 Simplifying x = -13
| 175x^2-28=0 | | 3a+9b-12= | | 4x+19=7-2x | | -5+4a+3a+6=0 | | 2x-8y=-34 | | -3(x-4)+10=-2 | | -49+9=-5 | | (7x+2)(3x-y)= | | 6(x+4)=3(4-2) | | x(7)=49 | | 2x^2=5-5x | | 3(2x-1)+9=2(3x+3) | | y=28(3)+10 | | 3.2-1.8x=-1.3 | | X^2+10=-25 | | -2x-7(-8x-16)=4 | | y=28x+10 | | 3.14*30*30*-=9420 | | 6-5x=-2 | | 3(5v+4)-(1-v)=-1+5v+1 | | -2x-7(8x-16)=4 | | 15=8-5(c+7) | | 18+y-1=16+y | | 4g=-16 | | N-6=50 | | 12n+2=-36 | | 2r-3=16+21 | | -.60(y-4)=-3 | | -7x-4(-8x-16)=-14 | | u+15=-13 | | x=.1x+5 | | 17x-7y=-5 |